Relationship between energy of pulsating auroral electrons and duct propagation of chorus wave: simultaneous observations with EISCAT radar, ground-based all-sky imagers, and Arase satellite - Ito, Yuri; Hosokawa, Keisuke; Ogawa, Yasunobu; Miyoshi, Yoshizumi; Fukizawa, Mizuki; Murase, Kiyoka; Oyama, Shin-ichiro; Nakamura, Satoko; Kasahara, Yoshiya; Matsuda, Shoya; Kasahara, Satoshi; Kazama, Yoichi; et al. (2022)
The 13th Symposium on Polar Science/Ordinary sessions [OS] Space and upper atmospheric sciences, Wed. 16 Nov. conference object